Komitmen Piagam Asean (Asean Charter) Dalam Melindungi Hak Dasar Warga Negara Di Asia Tenggara - Natamiharja, Rudi; Setiawan, Ikhsan (Fakultas Hukum Universitas Islam Indonesia, 2025)
ASEAN, as a regional organization, has sought to protect the fundamental rights of its citizens through the ASEAN Charter and various legal instruments. The commitment of the ASEAN Charter to protect the fundamental rights of citizens in Southeast Asia is evident. As a binding legal document, the ASEAN Charter aims to strengthen regional cooperation and promote respect for human rights, democracy, and the rule of law among ASEAN member states.Although ASEAN has established policies and institutions such as the ASEAN Intergovernmental Commission on Human Rights (AICHR) and the ASEAN Human Rights Declaration (AHRD), differences in political systems, the principle of non-intervention, and economic disparities among member states hinder the implementation of human rights protection. Countries with authoritarian systems find it more challenging to enforce policies, while economic disparities affect enforcement capacity in some nations.Other challenges include issues related to human trafficking, the protection of migrant workers, corruption, and institutional weaknesses. This research emphasizes the importance of a more coordinated approach and domestic reforms in ASEAN member states by strengthening regional mechanisms, engaging civil society, and enhancing international cooperation to ensure effective implementation of human rights protection in the region.